Current pharmacological treatments for COVID-19: A narrative review - Sudi Indra Jaya; Yacobus Christian Prasetyo (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
The coronavirus disease 2019 (COVID-19) pandemic has lasted more than one year. The number of daily cases and the number of deaths is still changing dynamically. As of this writing, specific drugs for COVID-19 are not yet available. This review aims to describe the key clinical evidence in pharmacological treatments for COVID-19. The article search process was carried out on the PubMed database with a combination of keywords ((“COVID-19”) OR (“SARS-CoV-2”)) AND ((“treatment”) OR (“therapy”)). In this article, there were six drugs reviewed that is corticosteroids, remdesivir, lopinavir-ritonavir, hydroxychloroquine, ivermectin, and interleukin-6 (IL-6) receptor blockers. Hydroxychloroquine, lopinavir-ritonavir, remdesivir, and ivermectin were not recommended for COVID-19 treatments regardless of disease severity and duration of symptoms. Therefore, they were excluded from the list of drugs for the treatment of COVID-19 by World Health Organization (WHO) stated strong recommendations in favor of two drugs, namely systemic corticosteroids and IL-6 receptor blockers namely tocilizumab or sarilumab. Both of them are recommended for the treatment of patients with severe and critical covid-19 so they are included in the list of COVID-19 therapeutic drugs by WHO.